Environment and Law, What Is the Indonesian Context? A Review Book 'Hukum Lingkungan Sebuah Pengantar untuk Konteks Indonesia', Prof. Dr. H. M. Hadin Muhjad, SH., M.Hum., PT Genta Publishing, Yogyakarta, 2015, 232 pages, ISBN: 978-602-1500-25-5 - Lestari, Berlian Putri Haryu (Indonesian Journal of Advocacy and Legal Services, 2021)
The environment consists of places or places, where there are various places of life such as the environment, natural environment, and others, in this book, explains that the environment is a place to live for the community, so do not be surprised if there are special requests or requests for the stability of nature. Direct Environment with nature, we can discuss the purpose of Environmental Law in this book because it has a language that is easily understood by every circumstance. In Chapter 1, this book explains about the Definition and Regulation of Environmental Law, What Is Environmental Law? According to this book, this proves that environmental law in a simple sense is the law that regulates the environmental order (Munadjat, 1980: 105). This book contains opinions about the term Environment that forms a new concept in Legal Science.